The Effect of the Jarimatika Method with the Problem Based Learning (PBL) Model on Third-Grade Students’ Basic Multiplication Skills at SD Negeri Sukanegara - Luheinul Zinan; Imam Bajuri (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study was motivated by the low basic multiplication skills of third-grade elementary school students, particularly in conceptual understanding, calculation accuracy, and problem-solving abilities. The objective of this study was to determine the effect of the Jarimatika method combined with the Problem Based Learning (PBL) model on students’ basic multiplication skills. This study employed a quantitative approach using a one-group pretest-posttest design. The participants were 30 third-grade students of SD Negeri Sukanegara. Data were collected through pretest and posttest instruments that had been tested for validity and reliability. The results showed a significant improvement in students’ multiplication skills after the treatment, as indicated by the increase in the mean score from 55.17 in the pretest to 80.00 in the posttest. The paired sample t-test analysis revealed a significant difference between pretest and posttest scores (t = -10.951, p = 0.000 < 0.05). The findings indicate that the implementation of the Jarimatika method combined with the Problem Based Learning (PBL) model effectively improves students’ basic multiplication skills and supports more active and meaningful mathematics learning.